Dry ultrasonic compaction of (Ba,Sr)TiO3 nanopowder for ceramics production; Korus 2000; Part 3 : Machine Parts and Materials Processing - Suk-Ryong Hahn; Khasanov O. L. Oleg Leonidovich; Pokholkov Y. P. Yuri Petrovich; Sokolov V. M. Vitaly Mikhailovich; Dvilis E. S. Edgar Sergeevich (2000, 2000)
The method of dry ultrasonic compaction was applied to press sol-gel ultrafine powder of (Ba,Sr)TiO3. Green compacts and sintered ceramics densities were compared depending on the powder compaction conditions (compaction pressure P, ultrasound power W). The grain size of sintered ceramics was analysed in dependence on the compaction conditions and sintering regimes (sintering temperature, holding time, heating rate). It was shown that dry ultrasonic compacting is possible for thin as well as thick green compacts with diameter of 50 mm. To make the most dense ceramics, the existence of optimum BST nanopowder compaction regimes was shown